(3EJeGe GdOQGjI dbQGA GdfbGjIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hHYO adeG XgQ dj JUhjH GdedMjf Ydj aj hVY TQM Ydi GdcQGSI GdJi SejJgG HGdfbGjI s
(3BNQgG (B:s
(3dGQGO dbVGFg HGdQaY hdGeoYbH dMceg HGdfbV SHMGfg hJYGdi Je GdTQM s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1970s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI HOeTb (B(9215) s
Keywords: (3GdeYGQa GdYGeIs